2022
DOI: 10.1051/bioconf/20224704001
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Asparagus officinalis L. through callus development

Abstract: In order to develop an in vitro propagation process for production and conservation, in this study, we investigated the influence of disinfectants and plants growth regulators (PGR) on the infection rate of explants, the ability of callus formation, and the regeneration of shoot and root from Asparagus officinalis L. trunk segments. We obtained the best results when disinfecting trunk segments explants combined with alcohol 70° in 5 minutes and NaClO in 5 minutes with the lowest contamination rate of 3.7%. Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It has also been reported that auxins alone can promote root formation in A. officinalis. For instance, Maung et al [15] showed that 2.5 mg/L IBA resulted in the highest rooting rate of 44%, while Minh et al [16] discovered that NAA at a concentration of 0.5 mg/L substantially improved the rooting rate by up to 74.59%. Considering the effect of CW on the in vitro rooting of A. officinalis, the concentrations of 5% and 10% (v/v) CW did not significantly induce root formation in the plant, but instead promoted root elongation, yielding approximately root lengths of 4.54 and 4.88 cm, respectively.…”
Section: Effect Of Coconut Water On Root Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that auxins alone can promote root formation in A. officinalis. For instance, Maung et al [15] showed that 2.5 mg/L IBA resulted in the highest rooting rate of 44%, while Minh et al [16] discovered that NAA at a concentration of 0.5 mg/L substantially improved the rooting rate by up to 74.59%. Considering the effect of CW on the in vitro rooting of A. officinalis, the concentrations of 5% and 10% (v/v) CW did not significantly induce root formation in the plant, but instead promoted root elongation, yielding approximately root lengths of 4.54 and 4.88 cm, respectively.…”
Section: Effect Of Coconut Water On Root Proliferationmentioning
confidence: 99%
“…Another study by Maung et al [15] reported that MS medium supplemented with 2.0 mg/L BAP produced the highest values for the number of shoots (9 shoots/explant), shoot length (2 cm), and number of nodes (2 nodes/shoot), while the highest rooting rate (40%) was observed in medium supplemented with 2.5 mg/L IBA. Most recently, Minh et al [16] demonstrated that MS medium supplemented with 2.0 mg/L BAP and 1.0 mg/L NAA resulted in the highest shoot formation rate (87.2%), while MS medium supplemented with 0.5 mg/L NAA yielded the highest rooting rate (74.59%) of in vitro A. officinalis plantlets.…”
Section: Introductionmentioning
confidence: 99%